A systematic review of economic evaluations for donor human milk versus standard feeding in infants - Mandana Zanganeh; Mary Jordan; Hema Mistry (Wiley, 2021)
Abstract Reviews on the cost/outcome of donor human milk (DHM) for infants requiring care in the neonatal intensive care unit (NICU) setting have been undertaken. However, the cost‐effectiveness evidence is unclear. Therefore, we conducted a systematic review of published full economic evaluations of DHM versus standard feeding in infants in neonatal care with the aim of undertaking a narrative synthesis of the cost‐effectiveness evidence and critical appraisal of the methods used. MEDLINE, EMBASE, Web of Science, Cochrane Library, Centre for Reviews and Dissemination (CRD) and PROSPERO databases were searched. Studies were included if they were full economic evaluations (model‐based or trial‐based), the participants were infants in neonatal units requiring nutritional support, the intervention was DHM and the comparator was any standard feeding option. There were no restrictions on outcome measures. Two authors independently assessed eligibility, extracted data, assessed quality and cross‐checked results, with disagreements resolved by consensus. Information extracted focused on study context, and economic evaluation methods and results. Of 2861 studies, seven were included. Six (86%) studies originated from high‐income countries. Four (57%) of the studies were model‐based. Although we could not directly compare the different studies, due to the heterogenous nature of health and economic parameters used in the studies, all DHM interventions indicated cost‐effective or cost saving results. This review suggests that economic evaluation of DHM interventions is an expanding area of research. Although these interventions show promise, future economic evaluations of DHM interventions need to explicitly provide more details on long‐term costs and consequences.